Public sector pay and adjustment : lessons from five countries - Colclough, Christopher (Routledge studies in development economics, 1997)
Case studies of Singapore, Korea, Zambia, Zimbabwe and Argentina show that in those countries which adjusted unsuccessfully real earnings declined sharply, often with a further negative impact on output.